Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1038/nrm2663
|View full text |Cite
|
Sign up to set email alerts
|

The evolving understanding of COPI vesicle formation

Abstract: The coat protein I (COPI) complex is considered to be one of the best-characterized coat complexes. Studies on how it functions in vesicle formation have provided seminal contributions to the general paradigm in vesicular transport that the ADP-ribosylation factor (ARF) small GTPases are key regulators of coat complexes. Here, we discuss emerging evidence that suggests the need to revise some long-held views on how COPI vesicle formation is achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 65 publications
4
63
0
1
Order By: Relevance
“…It is possible that Arf1•GTPgS could slow coatomer polymerization, implying a mechanism in which release of Arf1•GTP is required to ensure that cargo associates with coatomer prior to coatomer polymerization. This interpretation is consistent with the results reported by Hsu and colleagues 35,36,68 in which they found that the [R50K] ArfGAP1 did not efficiently generate COPI vesicles.…”
Section: Discussionsupporting
confidence: 83%
“…It is possible that Arf1•GTPgS could slow coatomer polymerization, implying a mechanism in which release of Arf1•GTP is required to ensure that cargo associates with coatomer prior to coatomer polymerization. This interpretation is consistent with the results reported by Hsu and colleagues 35,36,68 in which they found that the [R50K] ArfGAP1 did not efficiently generate COPI vesicles.…”
Section: Discussionsupporting
confidence: 83%
“…COPI, which is among the best-characterized coat complexes, is a cytosolic complex that coats Golgi-derived vesicles and is involved in protein transport from the Golgi apparatus to the endoplasmic reticulum via recruitment by Arf1. [21][22][23] Although the precise cellular mechanisms of COPI, and circulating COPE-Ab, in patients with OSA were not revealed by the current study, lipid inflammation might be a key element associated with elevated COPE-Ab levels in this patient population. Previous studies have reported that the Arf1-COPI vesicular transport machinery regulates droplet morphology and lipid storage/utilization within the vesicle-trafficking pathway.…”
Section: 16mentioning
confidence: 75%
“…In cell assays, brefeldin disrupts the Golgi complex, in part by ADP-ribosylating a protein called BARS (brefeldin A ADP-ribosylated substrate) which is necessary for vesicle fission (91). However, in a rat brain model, brefeldin did not directly act on BARS but was first endowed with an ADP-ribose moiety provided by CD38 (92), opening an exciting new avenue of research into the possible therapeutic uses of brefeldin in CD38 hi tumor cells.…”
Section: Connections No 2: Arcs and Other Nad-consuming Enzymesmentioning
confidence: 99%